Channel and tubular electrodes - Compton, R; Unwin, P (1986)
The application of channel electrodes and tubular electrodes as simple well-characterised, easy-to-use hydrodynamic electrodes is reviewed (99 references). Mass Transport in these electrodes is discussed along with the way in which this is achieved experimentally. Various electrochemical techniques used in conjunction with the electrodes are reviewed. The role of the electrode in studying electrode reactions coupled with homogeneous chemical reactions is particularly emphasized.